2016
DOI: 10.1080/19390211.2016.1205701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fish Oil Supplementation on Postresistance Exercise Muscle Soreness

Abstract: The aim of this study was to examine the effects of fish oil supplementation on the magnitude and time-course of postresistance exercise muscle soreness. This study was a randomized, placebo-controlled, double-blind trial. Nonresistance trained females were randomized into one of two groups: fish oil supplementation (6 g/day; 5:1 eicosapentaenoic acid to docosahexaenoic acid (EPA:DHA)) or placebo (6 g/day corn/soy oil). After consuming the supplements for one week, participants underwent a single bout of resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 9 publications
2
23
1
Order By: Relevance
“…Several previous studies, conducted in controlled laboratory settings, report a beneficial effect of fish oil supplementation on the perception of muscle soreness following intense eccentric exercise (Corder et al, 2016;Tsuchiya et al, 2016;Jouris et al, 2011;Lembke et al, 2014;Tinsley et al, 2016). Consistent with these experimental study findings, the present field-based study, which included a training protocol reflective of professional rugby with progressive resistance training and high volumes of anaerobic training, revealed a moderately beneficial effect of fish oil ingestion on muscle soreness during preseason Rugby training.…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies, conducted in controlled laboratory settings, report a beneficial effect of fish oil supplementation on the perception of muscle soreness following intense eccentric exercise (Corder et al, 2016;Tsuchiya et al, 2016;Jouris et al, 2011;Lembke et al, 2014;Tinsley et al, 2016). Consistent with these experimental study findings, the present field-based study, which included a training protocol reflective of professional rugby with progressive resistance training and high volumes of anaerobic training, revealed a moderately beneficial effect of fish oil ingestion on muscle soreness during preseason Rugby training.…”
Section: Discussionmentioning
confidence: 98%
“…Concerning muscle soreness, controversial findings have been reported on the effects of omega-3 intake on DOMS after eccentric exercise [17,18,34,35]. Many studies have reported a decrement of DOMS after EPA and DHA intake [17,18], but no change was observed after 2-4 weeks of single intake of DHA (0.8-2 g/day) [15,19].…”
Section: Discussionmentioning
confidence: 99%
“…A study has reported that the results of daily ingestion of 2,000-mg EPA and 1,000-mg DHA for 2 weeks signi cantly mitigated DOMS in the upper arm after two sets of ECCs (until exhaustion) via elbow exions using dumbbells at an intensity of 120% 1RM 22 . Similarly, as a result of 3,600 mg of EPA and DHA ingested for 2 weeks have also been reported to mitigate DOMS in the upper arm and thigh after 10 sets of ECCs (until exhaustion) through elbow exions and knee extensions at an intensity of 50% 1RM 23 . Studies using 8-week consumption of EPA and DHA at lower doses (600 mg/day of EPA and 260 mg/day of DHA) have reported signi cant mitigation of DOMS after 30 isokinetic ECCs by elbow exions 7 and DOMS after isotonic ECCs using dumbbells at an intensity of 40% 1RM 9 .…”
Section: Discussionmentioning
confidence: 91%